Seroprevalence of anti-TRYPANOSOMA CRUZI and anti-TOXOPLASMA GONDII antibodies in possible and potential organ donors in the south of Rio Grande do Sul state, Brazil - da Paz Grala, Ana Paula; Freitas Bianchi, Tanise; Ferreira de Leon, Italo; Guellamann da Cunha Espinelli Greco, Mayara; Raphael Pascoti Bruhn, Fabio; Celoi Ferreira Barargan, Nivia; Aspirot Mendonça, Viviani; Marreiro Villela, Marcos (Revista de Patologia Tropical / Journal of Tropical Pathology, 2020)
Serological profiles are important in cases of solid organ donation where serological findings, such as antibodies against Trypanosoma cruzi and toxoplasmosis, may interfere in organ donation by increasing morbidity and mortality. This study aimed to outline seroprevalence of anti-Trypanosoma cruzi and anti-Toxoplasma gondii antibodies in possible and potential organ donors in the south of Rio Grande do Sul (RS) State, Brazil. A cross-sectional quantitative and retrospective epidemiological study was carried out, based on secondary data. Data on serology were extracted from medical records found in the Sistema de Gestão Hospitalar (SIGH), a hospital management system used by a university hospital in the south of RS, Brazil. Sociodemographic variables, such as age, sex and race, as well as clinical variables, such as titration of IgM and IgG anti-T. cruzi and anti–T. gondii antibodies, were analyzed. Medical records were found to be poorly filled in, since 67.6% (506 records) could not be used due to lack of information. Seroprevalence of T. cruzi was 6.8% (5 cases), mostly in white males. Regarding seroprevalence of T. gondii, 76.2% (64 donors) were serologicaly positive, 10.9% of which were IgM positive. This is the first study on anti-T. cruzi and anti-T. gondii antibodies in organ donors in RS, Brazil and should be furthered since there may be consequences regarding organ uptake and donation. KEY WORDS: Epidemiological studies; Trypanosoma cruzi; Toxoplasma gondii; organ donation